Improving biology achievement using chart-based instruction among pre-service teachers - Onipede, Joy Abiola; Ariba, Blessing Aderibigbe; Ogunleye, Abayomi Taiwo; Adelakun, Kabir Adekunle; Olabode, Johnson Oluwasaanumi (Assimilation: Indonesian Journal of Biology Education, 2025)
The research examines the application of charts by pre-service educators in the instruction of biology and its impact on students’ achievement. A descriptive research methodology was employed to evaluate the utilization of charts by pre-service teachers specializing in Biology. The subsequent phase of the investigation utilized a pretest-posttest, non-equivalent control group design to explore the influence of chart utilization on student achievement in Biology. Data was analyzed using descriptive statistics to answer the research questions while Analysis of Covariance (ANCOVA) was used to test the hypotheses. Findings revealed that 51.8% of pre-service teachers frequently utilize charts in biology teaching. The result further revealed a statistical significant effect of charts on students' achievement in biology, with F(1,235) = 146.286 and p 0.05. Meanwhile, results showed that there was no significant main effect of gender on students’ achievement in biology, F(1,235) = 0.058, p 0.05, using chart-based instruction. Findings further revealed that there was no interaction effect of treatment (chart-based instruction) and gender on students’ academic achievement in biology (F(1,235) = 0.363, p   0.05. Findings from this study had provided insights for institutions in teacher training programmes on the importance of incorporating visual aid training for the pre-service teachers, as it had proven to increase their teaching confidence, effectiveness, and students’ achievement in biology.